2020
DOI: 10.3390/en13082095
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Analysis of the Thermal Performances of SiC/Water and Al2O3/Water Nanofluid Inside a Circular Tube with Constant-Increased-PR Twisted Tape

Abstract: The simultaneous use of two passive methods (twisted tape and a nanofluid) in a heat transfer system will increase the average Nusselt number (Nu) of the system. However, the presence of inserts and nanoparticles inside the tube will create higher pressure drop (ΔP) in the system, which can eventually affect the overall enhancement ratio (η), especially at higher Reynolds numbers (Re). Several modifications of twisted tapes have been made to reduce ΔP, but most showed a decreasing trend of η as Re increased. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The increase in the volume concentration increases the thermal conductivity [53] of the nanofluid, which in turn promotes more convective heat transfer due to nano clustering and Brownian motion. The mechanisms [54,55] responsible for heat transfer enhancement by inserts were one and the same for both patterns; however, the backward pattern inserted into the test section had more contact surface area, leading to additional blockage of the working fluid and offering increased turbulence in succession with more heat transfer augmentation being achieved than that forward pattern. The heat transfer enhancement summarized for the both patterns of conical strip inserts, different twist ratios, and vol.% concentrations is presented in Table 4.…”
Section: The Effect Of the Staggered Conical Strip Insert With Both F...mentioning
confidence: 93%
“…The increase in the volume concentration increases the thermal conductivity [53] of the nanofluid, which in turn promotes more convective heat transfer due to nano clustering and Brownian motion. The mechanisms [54,55] responsible for heat transfer enhancement by inserts were one and the same for both patterns; however, the backward pattern inserted into the test section had more contact surface area, leading to additional blockage of the working fluid and offering increased turbulence in succession with more heat transfer augmentation being achieved than that forward pattern. The heat transfer enhancement summarized for the both patterns of conical strip inserts, different twist ratios, and vol.% concentrations is presented in Table 4.…”
Section: The Effect Of the Staggered Conical Strip Insert With Both F...mentioning
confidence: 93%
“…In the work of Ahmad et al [6], both a numerical investigation (using Ansys Fluent) and experimental analysis were carried out to evaluate the thermal performance of SiCwater and Al 2 O 3 -water nanofluids inside a circular tube with constantly increased PR twisted tape. The main results of their study were an increase in heat transfer performance.…”
Section: Overviewmentioning
confidence: 99%
“…Several twisted tape designs have been proposed to enhance heat transfer with a reasonable pressure drop increase to improve thermal performance [21][22][23][24][25][26][27]. Wijayanta et al [21] numerically studied single-phase flow inside an enhanced tube equipped with square-cut twisted tapes at various twist ratios (y/W) of 2.7, 4.5, and 6.5 for the Reynolds number range of 8000 to 18,000, with water as the working fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum thermal performance factor offered by the modified twisted tapes was as high as 1.23, which was greater than that of a typical twisted tape (1.18). Ahmad et al [22] utilized twisted tapes with increasing and decreasing pitch ratios in SiC/water and Al 2 O 3 /water nanofluid flows. They observed that using twisted tapes with increasing pitch ratios better enhanced swirling flow with smaller pressure losses than ones with decreasing pitch ratios, especially near the outlet region.…”
Section: Introductionmentioning
confidence: 99%